A prospective study of the consulting behaviour of older people with knee pain - Jordan, Kelvin (Oxford University Press, 2006)
BACKGROUND: Knee pain is common among older adults but only a minority consult their doctor about it. AIM: To determine predictors of new episodes of consultation in primary care among older people with knee pain. DESIGN OF STUDY: Population-based prospective cohort study linking baseline survey to primary care medical records. SETTING: Three general practices in North Staffordshire, UK. METHOD: Subjects were 1797 people aged >50 years who responded to a general population survey, reported knee pain in the previous 12 months and had no record of a knee disorder consultation in the 18 months prior to the survey. The main outcome measure was a record of a knee disorder consultation in the 18 months following the survey. RESULTS: The incidence of a new episode of general practice care was approximately 10% per year. Apart from chronicity (odds ratio [OR] = 1.5; 95% confidence interval [CI] = 1.1 to 2.1), measures of pain severity were not strong influences on future consultation. No social support (measured by having no partner) increased likelihood of future consultation (OR = 1.3; 95% CI = 1.0 to 1.8). Among those with chronic and severe pain, main predictors were previous experiences of health care (use of non-GP services OR = 1.8; previous knee injury OR = 1.7). Current depression reduced likelihood of consulting about the knee problem (OR = 0.6; 95% CI = 0.3 to 0.9). CONCLUSIONS: Knee pain is common in the older population but a minority consult their doctor about it. Severity of pain and disability is not a strong influence on consultation. For those more severely affected, depression may act as a barrier to healthcare use.